2020
DOI: 10.1108/jima-11-2019-0243
|View full text |Cite
|
Sign up to set email alerts
|

Halal standard implementation in food manufacturing SMEs: its drivers and impact on performance

Abstract: Purpose The purpose of this paper is to investigate the drivers of the depth of halal standard implementation in the halal-certified food manufacturing small- and medium-sized enterprises (SMEs). The second aim of this paper is to empirically examine the effect of halal standard practices on the SME’s performance. Design/methodology/approach Of the 143 halal-certified SMEs in Solo Raya, Province of Central Java, Indonesia, 83 were willing to take part in the present research. The survey was carried out by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 71 publications
5
57
1
3
Order By: Relevance
“…The results of this study support the results of previous studies on quality management in general (Hassan et al, 2012;Raja et al, 2011;Witjaksono, 2012;Yunis et al, 2013), as well as halal quality management (Ab Talib et al, 2017;Giyanti et al, 2021;Salindal, 2019). Halal food products and services are related not only to the use of halal materials and production processes, but also to build trust, halal supply chains, halal packaging and storage, understanding customer needs (Ab Talib et al, 2017;Giyanti et al, 2021;Salindal, 2019). Halal industrial products have potentials in the new normal era due to the increasing consumer demand for products that are processed, stored, distributed with hygienic and halal standards.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of this study support the results of previous studies on quality management in general (Hassan et al, 2012;Raja et al, 2011;Witjaksono, 2012;Yunis et al, 2013), as well as halal quality management (Ab Talib et al, 2017;Giyanti et al, 2021;Salindal, 2019). Halal food products and services are related not only to the use of halal materials and production processes, but also to build trust, halal supply chains, halal packaging and storage, understanding customer needs (Ab Talib et al, 2017;Giyanti et al, 2021;Salindal, 2019). Halal industrial products have potentials in the new normal era due to the increasing consumer demand for products that are processed, stored, distributed with hygienic and halal standards.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the study found that the practice of halal quality management had a significant effect on the competitive advantage of Halal MSMEs (ρ<1%). The results of this study support the results of previous studies on quality management in general (Hassan et al, 2012;Raja et al, 2011;Witjaksono, 2012;Yunis et al, 2013), as well as halal quality management (Ab Talib et al, 2017;Giyanti et al, 2021;Salindal, 2019). Halal food products and services are related not only to the use of halal materials and production processes, but also to build trust, halal supply chains, halal packaging and storage, understanding customer needs (Ab Talib et al, 2017;Giyanti et al, 2021;Salindal, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations